LEAN PRODUCTION SYSTEM DEFINITION FROM THE PERSPECTIVE OF MALAYSIAN INDUSTRY - Amelia Natasya Abdul Wahab; Muriati Mukhtar; Riza Sulaiman (Asia-Pacific Journal of Information Technology and Multimedia, 2017)
"Muda" is a term in the Toyota Production System (TPS), which refers to waste that occurs in the manufacturing process. Waste is removed from the production process by eliminating activity that does not add value to the customer through a continuous improvement activities. This is the basis concept for TPS in order to produce products that meet customers's demand and requirements which then indirectly reduce the cost of production. Lean production concept has been implemented in various types of organizations. However, a low success rate for the implementation of lean production has become the attention of practitioners and researchers in the industry. Among the issues that contribute to this situation are confusion about the definition of lean and lack of knowledge on how to implement lean, which caused misunderstanding. In addition, there are no strategic planning and lack of support from the top management. Thus, the objective of this study is to develop a definition of lean from Malaysian context. The study is expected to help organizations implementing lean concepts with success and thus increasing the organizational competitiveness.